Indonesia's Socio-Economic Paradox: Generosity and Poverty - Adi Prawira; Ruslaini Ruslaini; Husni Fuaddi; Nasfi Nasfi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Indonesia, renowned for its strong philanthropic culture rooted in traditions like gotong royong and Islamic giving (zakat), paradoxically faces persistent poverty affecting over 60% of its population. This study explores the complex interplay between generosity and economic disparity in Indonesia by reviewing literature on financial inclusion, digital inequality, and poverty alleviation strategies. Despite notable economic growth and extensive charitable activities, structural issues such as unequal access to education, healthcare, and financial services particularly in rural areas continue to hinder inclusive development. The research highlights the limitations of traditional charity in addressing long-term poverty and underscores the importance of integrated approaches that combine government policy, technological advancement, financial literacy, and community empowerment. Strengthening digital infrastructure, expanding access to financial services, and supporting small and medium enterprises are identified as crucial pathways toward reducing inequality. The study concludes that aligning Indonesia’s philanthropic spirit with inclusive development strategies is essential to achieving sustainable poverty alleviation and economic resilience.